Survey of control and management mechanisms for time-sensitive network - Shuo WANG; Shuwen YIN; Hua LU; Jidong ZHANG (网络与信息安全学报)
Time-sensitive network can provide deterministic transmission services with bounded low latency for applications.Besides, it brings a unified architecture and standards to heterogeneous real-time Ethernet in the industry.However, the implementation and deployment of time-sensitive network based on IEEE Std 802.1Qcc face many challenges in various application scenarios.The research on the control and management mechanisms in time-sensitive network was summarized.Then the problems to be solved were analyzed and summarized from transmission performance, scalability and technology fusion.The latest research progress of control and management mechanisms was shown.The open issues and future research directions were discussed.